Longitudinal study assessing the return of chloroquine susceptibility of Plasmodium falciparum in isolates from travellers returning from West and Central Africa, 2000–2011 - Gharbi, Myriam (BioMed Central, 2013)
BACKGROUND: Chloroquine (CQ) was the main malaria therapy worldwide from the 1940s until the 1990s. Following the emergence of CQ-resistant Plasmodium falciparum, most African countries discontinued the use of CQ, and now promote artemisinin-based combination therapy as the first-line treatment. This change was generally initiated during the last decade in West and Central Africa. The aim of this study is to describe the changes in CQ susceptibility in this African region, using travellers returning from this region as a sentinel system. METHODS: The study was conducted by the Malaria National Reference Centre, France. The database collated the pfcrtK76T molecular marker for CQ susceptibility and the in vitro response to CQ of parasites from travellers’ isolates returning from Senegal, Mali, Ivory Coast or Cameroon. As a proxy of drug pressure, data regarding CQ intake in febrile children were collated for the study period. Logistic regression models were used to detect trends in the proportions of CQ resistant isolates. RESULTS: A total of 2874 parasite isolates were genotyped between 2000–2011. The prevalence of the pfcrt76T mutant genotype significantly decreased for Senegal (from 78% to 47%), Ivory Coast (from 63% to 37%), Cameroon (from 90% to 59%) and remained stable for Mali. The geometric mean of the 50% inhibitory concentration (IC(50)) of CQ in vitro susceptibility and the proportion of resistant isolates (defining resistance as an IC50 value > 100 nM) significantly decreased for Senegal (from 86 nM (59%) to 39 nM (25%)), Mali (from 84 nM (50%) to 51 nM (31%)), Ivory Coast (from 75 nM (59%) to 29 nM (16%)) and Cameroon (from 181 nM (75%) to 51 nM (37%)). Both analyses (molecular and in vitro susceptibility) were performed for the 2004–2011 period, after the four countries had officially discontinued CQ and showed an accelerated decline of the resistant isolates for the four countries. Meanwhile, CQ use among children significantly deceased in this region (fixed effects slope = −0.3, p < 10(-3)). CONCLUSIONS: An increase in CQ susceptibility following official withdrawal of the drug was observed in travellers returning from West and Central African countries. The same trends were observed for molecular and in vitro analysis between 2004-2011and they correlated to the decrease of the drug pressure.